Phonetical Relations of Reference-Inference in Wangsalan Sindhenan - Wijoyanto, Danang; Adipitoyo, Sugeng; Pairin, Udjang (Proceeding of International Joint Conference on UNESA, 2025)
Phonetic relations of reference-inference in wangsalan sindhenan is the speaker's act of referring to the wangsalan karep as an inference through the affinity of the sound of the cangkriman bars as a reference with the aim of knowing the contents of the wangsalan conveyed by the speaker. Inference is the speaker's process of obtaining non-literal additional knowledge based on the form of the spoken language and the characteristics of the context as an effort to find out the speaker's intent. Reference success is greatly influenced by inference. Successful referencing means that an intent can be identified through inference/conclusion. It shows a kind of knowledge that is shared and from here social relations occur. Inference in wangsalan is the process of speakers obtaining stems based on context and context as an effort to find wangsalan's intent. The aim of this study is to describe the types of reference-inference phonetic relationships in the sindhenan dynasty. The phonetic reference-inference relationship in wangsalan sindhenan is based on crossing the positioning of syllable sounds in a word into eight, namely (a) sound positioning relations at beginning-beginning, (b) sound positioning relations at beginning-mid, (c) sound positioning relations at mid-beginning, (d) sound positioning relations at mid-mid, (e) sound positioning relations at mid-end, (f) sound positioning relations at beginning-end, (g) sound positioning relations at end-mid, and (h) sound positioning relations at end-end.